The anatomical structure of the root, stem, and branch of Gyrinops versteegii trees from different growing sites - ARIEL ADIMAHAVIRA; GANIS LUKMANDARU; RINI PUJIARTI; FANANY WURI PRASTIWI; WIDYANTO DWI NUGROHO (Society for Indonesian Biodiversity, 2023)
Abstract. Adimahavira A, Lukmandaru G, Pujiharti R, Prastiwi FW, Nugroho WD. 2023. The anatomical structure of the root, stem, and branch of Gyrinops versteegii trees from different growing sites. Biodiversitas 24: 4590-4598. Gyrinops versteegii (Gilg) Domke is an agarwood (Gaharu)-producing species with a unique color and very expensive fragrance. Even so, studies on the effects of growing sites on the wood anatomical structure of several parts of G. versteegii have not been thoroughly investigated. Therefore, this research aims to investigate the anatomical structure of G. versteegii on the tree's root, stem, and branch at two different growing sites. Three five-year-old G. versteegii trees from Pacitan and Klaten Districts (Indonesia) were used for the experiment and were harvested from the root, stem, and branch. The wood samples were then put in a glutaraldehyde solution for 24 hours and later in an alcohol solution. The samples were sliced in microtome (15-20 µm) and observed in the transverse, tangential, and radial sections. The results showed that the anatomical characteristics, such as vessel diameter, ray height, ray frequency, interxylary phloem proportion, and frequency differed significantly between growing sites. Furthermore, fiber length, vessel diameter, ray height, ray frequency, and interxylary phloem proportion significantly differed among plant parts. In addition, the branch part has the highest interxylary phloem value, indicating the possibility of a high agarwood resin deposit when agarwood stimulation is applied.